Islamic Family Counseling to Enhance Family Harmony in the Modern Era - Ernaeny, Windy; Murtadho, Ali; Wati, Levinia Dian Kristina; Is Haque, Aptaarkhan Aurell (International Journal of Religious and Interdisciplinary Studies, 2025)
Family harmony is a crucial foundation in social life, particularly within Islamic culture and values. In the modern era, communication breakdowns, value differences, and life stressors often disrupt relationships between spouses and extended family members. Islamic family counseling, rooted in Sharia principles and Islamic ethics, offers a structured approach to strengthening family bonds amidst these social changes. This study aims to explore the role of Islamic family counseling in enhancing family harmony in contemporary society. Utilizing a qualitative phenomenological method with narrative analysis, data were gathered through in-depth interviews and field observations involving Muslim families in Semarang who had sought counseling services. The findings reveal that Islamic family counseling significantly improves communication skills, conflict management, and internalizing Islamic values within families. It emphasizes active listening, patience, forgiveness, and integrating worship and community bonding practices into daily life. These techniques contribute to emotional stability and the spiritual resilience of families facing modern challenges. This study offers practical recommendations for improving Islamic family counseling services and highlights its vital contribution to sustaining family harmony in a rapidly changing world.